1996
DOI: 10.1108/01443579610119108
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the use of just‐in‐time purchasing in a developing country

Abstract: IntroductionAs cost becomes increasingly important in today's highly competitive international marketplace, more and more companies find themselves moving at least parts of their manufacturing operations to developing countries. This highly competitive marketplace, though, allows few of these companies to compete solely on the basis of price. To be successful, these companies must also achieve high levels of quality and be responsive to changing market needs. One approach that many companies in more developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 5 publications
6
14
0
Order By: Relevance
“…the Lawrence and Lewis (1996) study and the Wafa and Yasin (1998) study. The modifications made to these studies were determined by the researcher's own knowledge of conditions of the Egyptian industrial sector and the theoretical issues discussed previously.…”
Section: Study Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…the Lawrence and Lewis (1996) study and the Wafa and Yasin (1998) study. The modifications made to these studies were determined by the researcher's own knowledge of conditions of the Egyptian industrial sector and the theoretical issues discussed previously.…”
Section: Study Methodologymentioning
confidence: 99%
“…Lawrence and Lewis (1996) concluded in their study of the use of JIT practices in Mexico that JIT can be used successfully in some Mexican manufacturing firms. Furthermore, they found that there are three groups of obstacles that hinder the implementation of JIT in Mexican operations:…”
Section: Jit Benefits and Pitfallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fawcett and Scully (1995) provide evidence about a direct relationship between JIT purchasing implementation and cost-oriented benefits such as reduced administrative costs, inspection costs and inventory costs, as well as non-cost-oriented benefits such as design, quality, productivity and scheduling improvements. In a study of manufacturing plants in Mexico, Lawrence and Lewis (1996) noted a positive relationship between the implementation JIT purchasing practices related to logistics and supplier involvement and the results of the firm as regards aspects such as quality, customer service and productivity. Ansary and Heckel (1987) and Schonberger and Ansari (1984) explain respectively how some companies have reduced logistics costs and improved Spanish auto components industry 1047 quality by means of JIT purchasing.…”
Section: Hypothesesmentioning
confidence: 99%
“…To remove those obstacles, a project management approach was implemented and, as we expected, productivity and quality for the case study went up, and lead-time went down from six in less than two months. Lawrence and Lewis (1996) reported that poor supplier bases and infrastructures pose significant barriers for the implementation of just-in-time (JIT) purchasing in developing countries. They analyzed two distinct activities characteristic of JIT purchasing, which includes JIT deliveries from suppliers and supplier involvement in improvement activities in Mexican industries.…”
Section: Introductionmentioning
confidence: 99%